Using general practice clinical information system data for research: the case in Australia - Youens, David; Moorin, Rachael; Harrison, Amy; Varhol, Richard; Robinson, Suzanne; Brooks, Caroline; Boyd, James (International Journal of Population Data Science, 2020)
General practice is often a patient’s first point of contact with the health system and the gateway to specialist services. In Australia different aspects of the health system are managed by the Commonwealth Government and individual state/territory governments. Although there is a long history of research using administrative data in Australia, this split in the management and funding of services has hindered whole-system research. Additionally, the administrative data typically available for research are often collected for reimbursement purposes and lack clinical information. General practices collect a range of patient information including diagnoses, medications prescribed, results of pathology tests ordered and so on. Practices are increasingly using clinical information systems and data extraction tools to make use of this information. This paper describes approaches used on several research projects to access clinical, as opposed to administrative, general practice data which to date has seen little use as a resource for research. This information was accessed in three ways. The first was by working directly with practices to access clinical and management data to support research. The second involved accessing general practice data through collaboration with Primary Health Networks, recently established in Australia to increase the efficiency and effectiveness of health services for patients. The third was via NPS MedicineWise’s MedicineInsight program, which collects data from consenting practices across Australia and makes these data available to researchers. We describe each approach including data access requirements and the advantages and challenges of each method. All approaches provide the opportunity to better understand data previously unavailable for research in Australia. The challenge of linking general practice data to other sources, currently being explored for general practice data, is discussed. Finally, we describe some general practice data collections used for research internationally and how these compare to collections available in Australia. Keywords: General practice; administrative data; big data, health information systems, medical records systems